What Is the Optimal Treatment for Liver Hydatid Cysts in Emergency and Elective Situations? - Zerem, Enver; Puljiz, Željko; Zdilar, Boris; Kunosić, Suad; Kurtcehajic, Admir; Zerem, Omar (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Zerem E, Puljiz Ž, Zdilar B, Kunosić S, Kurtcehajic A, Zerem O. What is the optimal treatment for liver hydatid cysts in emergency and elective situations? Turk J Gastroenterol. 2024;35(2):158-159.